Laparoscopic Repair of Congenital Diaphragmatic Hernia in Adults. (15th December 2016) - Saroj, Sanjay Kumar; Kumar, Satendra; Afaque, Yusuf; Bhartia, Abhishek Kumar; Bhartia, Vishnu Kumar
Abstract : Background, Aims, and Objectives . Congenital diaphragmatic hernia typically presents in childhood but in adults is extremely rare entity. Surgery is indicated for symptomatic and asymptomatic patients who are fit for surgery. It can be done by laparotomy, thoracotomy, thoracoscopy, or laparoscopy. With the advent of minimal access techniques, the open surgical repair for this hernia has decreased and results are comparable with early recovery and less hospital stay. The aim of this study is to establish that laparoscopic repair of congenital diaphragmatic hernia is a safe and effective modality of surgical treatment. Materials and Methods. A retrospective study of laparoscopic diaphragmatic hernia repair done during May 2011 to Oct 2014. Totaln = 13 (M/F: 11/2) cases of confirmed diaphragmatic hernia on CT scan, 4 cases Bochdalek hernia (BH), 8 cases of left eventration of the diaphragm (ED), and one case of right-sided eventration of the diaphragm (ED) were included in the study. Largest defect found on the left side was 15 × 6 cm and on the right side it was 15 × 8 cm. Stomach, small intestine, transverse colon, and omentum were contents in the hernial sac. The contents were reduced with harmonic scalpel and thin sacs were usually excised. The eventration was plicated and hernial orifices were repaired with interrupted horizontal mattress sutures buttressed by Teflon pieces. A composite mesh was fixed with nonabsorbable tackers. All patients had good postoperative recovery and went home early with normal follow-up and were followed up for 2 years. Conclusion. The laparoscopic repair is a safe and effective modality of surgical treatment for congenital diaphragmatic hernia in experienced hands.